Mangroves in the Galapagos islands: Distribution and dynamics - Moity, Nicolas; Delgado, Byron; Salinas-de-León, Pelayo (PLOS ONE, 2019)
Mangrove forests provide valuable coastal protection from erosion, habitat for terrestrial and marine species, nursery grounds for commercial fisheries and are economically important for tourism. Galapagos’ mangroves usually grow directly on solid lava and fragmented rocky shores, thereby stabilizing the sediment and facilitating colonisation by other plants and many animals. However, until very recently, only inaccurate data described mangrove coverage and its distribution. We mapped mangroves using freely available Google Earth Very High Resolution images based on on-screen classification and compared this method to three semi-automatic classification algorithms. We also analysed mangrove change for the period 2004–2014. We obtained an area of 3657.1 ha of fringing mangrove that covers 35% of the coastline. Eighty percent of mangrove cover is found in Isabela island, and 90% in the western and central south-eastern bioregions. The overall accuracy of mangrove classification was 99.1% with a Kappa coefficient of 0.97 when validated with field data. On-screen digitization was significantly more accurate than other tested methods. From the semi-automated methods, Maximum Likelihood Classification with prior land-sea segmentation yielded the best results. During the 2004–2014 period, mangrove coverage increased 24% mainly by expansion of existing mangroves patches as opposed to generation of new patches. We estimate that mangrove cover and growth are inversely proportional to the geological age of the islands. However, many other factors like nutrients, currents or wave exposure protection might explain this pattern. The precise localization of mangrove cover across the Galapagos islands now enables documenting whether it is changing over time.